2014
DOI: 10.2105/ajph.2014.301894
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Texting Laws on Motor Vehicular Fatalities in the United States

Abstract: Using a panel study design, we examined the effects of different types of texting bans on motor vehicular fatalities. We used the Fatality Analysis Reporting System and a difference-in-differences approach to examine the incidence of fatal crashes in 2000 through 2010 in 48 US states with and without texting bans. Age cohorts were constructed to examine the impact of these bans on age-specific traffic fatalities. Primarily enforced laws banning all drivers from texting were significantly associated with a 3% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Primary enforced laws banning all drivers from texting was associated with a 3% reduction in fatalities in all age groups; banning only young drivers from texting had the greatest impact on reducing deaths among those aged 15 to 21 years (Ferdinand et al, 2014). A similar study found an 8% decrease in fatalities in states that universally banned texting while driving and made it a primary offense.…”
Section: Effectiveness Of Current Mitigation Strategiesmentioning
confidence: 99%
“…Primary enforced laws banning all drivers from texting was associated with a 3% reduction in fatalities in all age groups; banning only young drivers from texting had the greatest impact on reducing deaths among those aged 15 to 21 years (Ferdinand et al, 2014). A similar study found an 8% decrease in fatalities in states that universally banned texting while driving and made it a primary offense.…”
Section: Effectiveness Of Current Mitigation Strategiesmentioning
confidence: 99%
“…However, enforcement of distracted driving laws can present significant challenges,18–21 and laws that are not regularly and strictly enforced are unlikely to deter behaviour 5. Some studies have examined the association between distracted driving laws and measures of distracted driving;22 23 however, to our knowledge, no prior studies have examined the enforcement of distracted driving laws through the perspective of law enforcement officers. The goal of this study was to identify multilevel interdependent factors that influence distracted driving enforcement through the perspective of police officers in Washington State.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that a texting ban was associated with the decreased number of fatalities and injuries due to motor vehicle crashes (Ferdinand et al, 2014, 2015), whereas other studies have shown that a texting ban was not associated with decreased frequencies of physically manipulating a phone while driving (Goodwin, O’Brien, & Foss, 2012), a reduction of motor vehicle crashes at all (Ehsani, Bingham, Ionides, & Childers, 2014), or a long-term reduction of motor vehicle crashes (Abouk & Adams, 2013). Educational campaigns, such as U Drive.…”
mentioning
confidence: 99%